In vivo activity of Sapindus saponaria against azole-susceptible and -resistant human vaginal Candida species - Svidzinski Terezinha IE; Donati Lucélia; Batista Márcia R; Bertoni Thâmara A; Ferreira Izabel CP; Cortez Diógenes AG; Tsuzuki Joyce K; Damke Edílson; Consolaro Márcia EL (BMC, 2011)
Abstract Background Study of in vivo antifungal activity of the hydroalcoholic extract (HE) and n-BuOH extract (BUTE) of Sapindus saponaria against azole-susceptible and -resistant human vaginal Candida spp. Methods The in vitro antifungal activity of HE, BUTE, fluconazole (FLU), and itraconazole (ITRA) was determined by the broth microdilution method. We obtained values of minimal inhibitory concentration (MIC) and minimum fungicide concentration (MFC) for 46 strains of C. albicans and 10 of C. glabrata isolated from patients with vulvovaginal candidiasis (VVC). VVC was induced in hyperestrogenic Wistar rats with azole-susceptible C. albicans (SCA), azole-resistant C. albicans (RCA), and azole-resistant C. glabrata (RCG). The rats were treated intravaginally with 0.1 mL of HE or BUTE at concentrations of 1%, 2.5% and 5%; 100 μg/mL of FLU (treatment positive control); or distilled water (negative control) at 1, 24, and 48 h after induction of the infection, and the progress of VVC was monitored by culturing and scanning electron microscopy (SEM). The toxicity was evaluated in cervical cells of the HeLa cell line. Results The extracts showed in vitro inhibitory and fungicidal activity against all the isolates, and the MIC and MFC values for the C. glabrata isolates were slightly higher. In vivo, the SCA, RCA, and RCG infections were eliminated by 21 days post-infection, with up to 5% HE and BUTE, comparable to the activity of FLU. No cytotoxic action was observed for either extract. Conclusions Our results demonstrated that HE and BUTE from S. saponaria show inhibitory and fungicidal activity in vitro, in addition to in vivo activity against azole-resistant vaginal isolates of C. glabrata and azole-susceptible and resistant isolates of C. albicans. Also considering the lack of cytotoxicity and the low concentrations of the extracts necessary to eliminate the infection in vivo, HE and BUTE show promise for continued studies with purified antifungal substances in VVC yeast isolates.